Intensitas Serangan Penyakit Antraknosa (Collectorichum sp.) pada Tanaman Cabai Merah (Capsicum annum) di Desa Tanjung Senai Kecamatan Indralaya Utara, Kabupaten Ogan Ilir - Salsabila Cahyami, Prima; Hamidson, Harman; Tricahyati, Titi; Arsi, Arsi; Suparman, Suparman; Melinda, Dhea; Agustia, Dinda; Br Saragih, Evi Suryani; Sulistianingsih, Putri; Rahmawati, Suci (Seminar Nasional Lahan Suboptimal, 2024)
Cahyami, P, S.,Hamidson, H., Tricahyati, T., Arsi, A., Suparman, S., Melinda, D., Agustia, D., Br Saragih, E. S., Sulistianingsih, P., Rahmawati, S.. (2024). Intensity of anthracnose (Colletotrichum sp.) attacks on red chili (Capsicum annum) plants in Tanjung Senai Village, North Indralaya District, Ogan Ilir Regency.In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembangg 21 Oktober 2024. (pp. 778–786). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Colletotrichum sp. Fungus is a plant pest organism (OPT) that can cause anthracnose disease in red chili plants (Capsicum annum) with damage reaching 80%. This study aimed to identify the level of anthracnose disease attacks in Tanjung Senai Village, North Indralaya District, Ogan Ilir Regency. The method used is purposive sampling with field observations for two months. The results show that the percentage of anthracnose attack severity varies, with land A experiencing 6.19%, land B 8.08%, and land C 13.19%. the highest disease growth rate occurred in land C with 39.92%. anthracnose disease attacks on chili plants increase with increasing plant age.